REMOVAL OF COMMERCIAL ANIONIC DETERGENT IN WATER USING CONTINUOUS PROCESS OF BIOLOGICAL REACTOR WITH ADDING OF PAC - Said, Nusa Idaman (Center for Environmental Technology, 2007)
Synthetic detergents, mostly anionic detergents have been widely used in IndonesiaÃ‚Â over past two decades, similar to its use in other developing countries, and residuals from such use have entered the country's riverine and estuarine systems. Detergent problems have become more serious especially in urban areas where the spread of sewerage systems are still low, even in drinking water treatment process. According to this reason, it is important to develop low-cost technology to solve this problem such as developing biological treatment for removing detergents.Effects OF continuous adding of powdeR activated carbon (PAC) on biological removal of anionic detergent in continuous reactor was assessed. Results of these experiments showed that introduction of PAC into biological treatment of anionic detergent (ABS or LAS), has indicated significant effect on removal efficiency. Conducting continuous feeding of PAC into bench scale of continuous process system for removal of detergent has resulted better stability of MBAS removal efficiency, even when MLSS concentration in aeration tank dropped or MBAS concentration in influent water rose rapidly. With continuous addition of PAC, the MBAS removal efficiency was relatively constant even when the water temperature dropped rapidly.Ã‚Â In other words, continuous feeding of PAC can improve the stability for shock loads or temperatures changes. At lower temperatures, micro organisms that were used for detergent removal in bench scale of continuous process system, need longer adaptation or acclimation periods compared with higher temperatures.Ã‚Â Key Words: Commercial anionic detergent, biodegradation, biological reactor, powdered activated carbon (PAC).